Besøget i Theresienstadt den 2.-4. marts 2015 - Fischermann, Robert (Rambam. Tidsskrift for jødisk kultur og forskning, 2017)
Visit in Theresienstadt The background of the article is Robert Fischermann’s visit to Terezin (Theresienstadt) in the spring of 2015. The occasion was the recording of a TV programme with former Danish prisoners of the concentration camp who had been there as children, and the visit was preceded by the recording of interviews with the participants in their present homes. The author reflects on the relation between his experiences in 1943-1945 and his emotions on re-visiting Terezin 70 years later, and he also wants to express his gratitude towards the team for all their consideration concerning the interview and the visit to an emotionally very charged location.